2009
DOI: 10.1111/j.1365-2591.2009.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of thin‐walled roots restored with different post systems

Abstract: Kıvanç BH, Alaç am T, Ulusoy Ö _ IA, Genç Ö , Gö rgü l G. Aim To compare the fracture resistance of thin-walled roots after restoration with different types of post systems.Methodology One hundred and sixty-five decoronated maxillary central incisors were root filled and randomly assigned to three groups with respect to the remaining dentine thickness of root (1.0 mm, 1.5 mm, 2.0 mm). Each group was randomly divided into five equal subgroups. The subgroups were restored with one of the following post systems: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
4
21
1
2
Order By: Relevance
“…Fracture strength The fracture strength of zirconia posts was evaluated using natural teeth in 15 studies 12,14,33,39,[41][42][43]48,49,51,55,58,[60][61][62] ( Table 1) and artificial roots in three studies 29,53,59) , and according to core material (composite resin core versus ceramic core) in nine studies 35,40,[44][45][46][47]52,54,57) (Table 2). Table 1 shows that the fracture strengths of teeth with zirconia posts and composite cores ranged between 300 N and 700 N. However, when ceramic cores were used, these values ranged between 800 N and 1500 N. These results concurred with studies which evaluated the fracture strength of zirconia posts according to core material 35,40,44,45,54) .…”
Section: Resultsmentioning
confidence: 99%
“…Fracture strength The fracture strength of zirconia posts was evaluated using natural teeth in 15 studies 12,14,33,39,[41][42][43]48,49,51,55,58,[60][61][62] ( Table 1) and artificial roots in three studies 29,53,59) , and according to core material (composite resin core versus ceramic core) in nine studies 35,40,[44][45][46][47]52,54,57) (Table 2). Table 1 shows that the fracture strengths of teeth with zirconia posts and composite cores ranged between 300 N and 700 N. However, when ceramic cores were used, these values ranged between 800 N and 1500 N. These results concurred with studies which evaluated the fracture strength of zirconia posts according to core material 35,40,44,45,54) .…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with previous studies[1921] that suggested that a smaller post-diameter might be used to avoid excessive wear of the inner root dentin during the post-site preparation once the amount of the remaining dentin wall around the post is directly related to the fracture resistance of the tooth. [192122] However, some studies indicated that posts with increased diameters were more resistant to fracture and provided more resistance to the restored teeth,[10] and led to less stress distribution to the remaining dentin. [11] In spite of these considerations, our study indicates a more conservative root canal preparation, being a 1.10-mm size (1/3 of the root) able to perform proper resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The high elastic modulus of Ni–Cr alloy compared with dentin, and its capability to concentrate stresses in critical areas of root, may be responsible for these catastrophic fractures. [1013152425] Conversely, glass-fiber posts have a lower elastic modulus, similar to that of dentin, distributing stresses more uniformly along the dentin/post-interface. [212425] The bonding between the fiber post and dentin root creates a “monobloc,” which is another factor that might contribute to a better stress distribution on the tooth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Glass fiber posts are an alternative for the restoration of teeth with IR due they have modulus of elasticity similar to dentine. 19,20 The use of an apical plug with MTA has been suggested for endodontic therapy of teeth with IR, [21][22][23] resulting in a faster treatment and inducing the mineralized tissue formation in the root apex. 24 The root canal filling using Epiphany/…”
Section: 10mentioning
confidence: 99%